Civil contract as an institution of civil law - Kolobylina, O. O. (Bulletin of Kharkiv National University of Internal Affairs, 2023)
The article argues that civil law is a branch of law which regulates property and personal non-property relations between individuals and/or legal entities based on the principles of equality, free expression of will and protection of rights and legitimate interests of participants to civil legal relations. Civil law includes rules that establish the basis for the creation, modification and termination of civil relations, as well as determine the procedure for the protection of violated civil rights. It has been stated that a civil contract as an institution of civil law is a voluntary agreement in which the parties to the contract express a single will aimed at establishing, changing or terminating civil rights and obligations and achieving certain civil law consequences in the appropriate form. The author identifies the following key features of a civil law contract (agreement): like any contract, it is concluded on a voluntary basis, however, its parties are equal and bear mutual responsibility for non-performance and/or improper performance of their obligations; the contract is personalised; stability of the contract (agreement) terms which remain in force until they are changed by agreement of the parties or until the contract expires in accordance with the stipulated terms; flexibility of terms and conditions, since the parties have the right to determine their own terms and conditions of the contract, in particular, price, terms, scope, etc.; the scope of a civil law contract is broad, and may include issues related to the sale and purchase of goods, services, loans, lease of property, etc.; a civil law contract is an important source of civil law.